Creative project-based learning model to increase creativity of vocational high school students - Usmeldi Usmeldi; Risda Amini (Institute of Advanced Engineering and Science, 2022)
The competence of vocational students in mastering electric motor installation was still low, because learning process has not involved student activities. One of the choices to activate students in learning was through project-based learning. Students were trained to be able to solve problems and make creative products. Project-based learning that applied in learning the Electric Motor Installation has not been able to increase students’ creativity in solving problems and make creative products. Therefore, research was carried to develop a project-based learning model into creative project-based learning. To support the implementation of the creative project-based learning model, teaching material is needed. The development of creative project-based learning use research and development method of 4D model of Thiagarajan with the stages of define, design, develop and disseminate. The research instruments were interview guides, observation sheets, questionnaires, skills assessment sheets, and test. Data analysis use percentage, gain score, and t-test. The research resulted a creative project-based learning model that was valid, practical and effective to improve student competence in Electric Motor Installation. The creative project-based learning model can increase students' creativity and competence in the form of mastery of teaching materials, skills in make the creative product and work attitudes.